The family of phytochrome-like photoreceptors: diverse, complex and multi-colored, but very useful. (December 2015) - Anders, Katrin; Essen, Lars-Oliver
Graphical abstract: Highlights: All three groups of phytochrome-like photoreceptors are structurally characterized. By color-fine tuning phytochromes cover the whole spectrum from UV to NIR. Phytochrome-like photoreceptors form a family with highly diverse photochemistries. Phytochromes' diversity makes them to interesting targets for synthetic biology. Abstract : Bilin-dependent GAF domain photoreceptors cover the whole spectrum of light with their absorbance properties. They can be divided into three groups according to the domain architecture of their photosensory module. Group I and Group II harbor phytochromes with PAS-GAF-PHY and GAF-PHY domain architecture, respectively. Group III consists of stand-alone GAF domain photoreceptors, the cyanobacteriochromes. Crystal structures of all three groups are now available to shed light on possible downstream signaling pathways. Structures of Group I and III photoreceptors in both states display changes in the secondary structures during photoconversion. The knowledge about the photoconversion in phytochromes and CBCRs make them promising targets for applications in life science and synthetic biology.